ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KETEPAT-WAKTUAN PENYAMPAIAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Marcelli, Fanny; Lasdi, Lodovicus (Widya Mandala Surabaya Catholic University, 2012)
The company must provide ease of provision of information to make a decision namely through the financial statement. Because of that, the financial statement must be submitted in a timeliness. If a company doesn’t provide timely reports of the financial state-ment, then the financial of the company could be losing power to provide information for its users. This quantitative descriptive research aims to examine and analyze the factors that influence the timeliness of the financial statement forwarding. The inde-pendent variables which used in this study was the company’s size, profitability, leverage, the size of the CPA, and the auditor’s opinion. The number of samples per year are 84 companies bringing the total to 252 companies that were observed and the tech-nique of data analysis in this study is using an analyze logistic regression. The results of this research indicated that the variable is the company’s size and the leverage had effect on the timeliness of the financial statement forwarding. However, the variable profitability, the size of the CPA, and the auditor’s opinion has no effect against the timeliness of the financial statement forwarding.